Isothermal solid-phase recombinase polymerase amplification on microfluidic digital versatile discs (DVDs). Issue 38 (27th March 2015) - Tortajada-Genaro, Luis A.; Santiago-Felipe, Sara; Amasia, Mary; Russom, Aman; Maquieira, Ángel
Abstract : The proposed device, for massive DNA-based screening in limited-resource settings, comprises a centrifugal platform to perform isothermal solid-phase amplification in microarray format and a digital versatile disc drive to read the results. Abstract : A new advancement in massive DNA-based screening in limited-resource settings is demonstrated through the incorporation of easy-to-fabricate microfluidic chambers on digital versatile discs (DVDs) to perform isothermal recombinase polymerase amplification (RPA) in a microarray format. Standard un-modified DVD discs and commercial drives are used for the low-cost detection method. DNA primers were printed in a microarray format on the polycarbonate surfaces of DVDs with integrated control spots to guarantee the absence of false-negatives and false-positives. The solid-phase amplification assay, including the washing protocols and development reaction, was performed by the dispensation of solutions through the inlet and by controlling the flow-movement by DVD drive centrifugation. The final disc with reaction products was inserted into a DVD player and microarray images were captured and automatically processed. This simple approach was applied for the screening of genetically modified organisms (GMOs) in food samples. The limit of detection was 7 μg g −1, which is well below the EU regulation limit for GMOs in food products. Therefore, the only required materials for food safety monitoring were standard store-bought DVDs, plastic chambers, tips, pipettes, an oven, and a standard DVD drive. The proposed strategy allows an integrated microarray system with low manipulation, reduced sample volume, and portability, which are beneficial for low-resource settings.